2022
DOI: 10.1002/sstr.202100233
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reconstruction of Ni‐Rich Layered Cathodes: In Situ Doping versus Ex Situ Doping

Abstract: The structural instability and sluggish Li+ diffusion kinetic of the nickel‐rich LiNixCoyMn1−x−yO2 (NCM) cathode still hinder its further commercialization for lithium‐ion batteries. Doping heteroatoms are widely studied as an effective strategy to maintain structural and thermal stability for improving the capacity retention of NCM during cycling. Herein this work, in situ Zn2+‐doped NCM (in situ Zn‐NCM) is successfully designed by atomic layer deposition (ALD) combined with annealing. In comparison to ex sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In addition to our prior work, the preference for the Zn-dopant toward occupying the Li-layer has also been subsequently reported by Wang et al On a different note, in the case of Zn-dopant, as compared to many other dopants explored to date, the solubility product constant of Zn­(OH) 2 is fairly similar to that of Ni­(OH) 2 , which renders it better feasible and facile to obtain Zn-doped Li-NMCs via the preferred co-precipitation route. , …”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition to our prior work, the preference for the Zn-dopant toward occupying the Li-layer has also been subsequently reported by Wang et al On a different note, in the case of Zn-dopant, as compared to many other dopants explored to date, the solubility product constant of Zn­(OH) 2 is fairly similar to that of Ni­(OH) 2 , which renders it better feasible and facile to obtain Zn-doped Li-NMCs via the preferred co-precipitation route. , …”
Section: Introductionsupporting
confidence: 76%
“…The initial shift of the (003) peak position toward the lower angle is by only ∼0.01° for the Zn-doped Li-NMC, as compared to ∼0.16° for the undoped counterpart (see Figures b and d). This corresponds to dilation of the “ c ” lattice parameter by ∼0.295 Å for the undoped Li-NMC, with that for the Zn-doped counterpart being just by ∼0.014 Å (compare Figure b,d), which is believed to be due to the constant screening effect of the inactive and stable Zn 2+ ions located in the Li-layer. , More importantly, absolutely no indication of the detrimental shrinkage/“collapse” of the c -axis parameter is obtained from the operando diffraction data, even at the very high states of charges (i.e., even upon deep delithiation up to 4.7 V) (see Figures b and d). This is likely to be again due to the “pillaring” effect of the Zn-ions that are present mainly in the Li-layer of the Zn-doped Li-NMC (see Sections , , Figure S4, and Table S2 in the Supporting Information and our previously published study).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure S4b, the peaks in the range of 529.4–532.9 eV are due to the lattice oxygen (TM-O), OV, and chemisorbed oxygen in turn. Compared with the pristine sample, the 3P-LRMO modified by NaH 2 PO 2 contains more OVs along with slightly less lattice oxygen content. …”
Section: Resultsmentioning
confidence: 99%
“…Surface doping and surface modification strategies have been proven to be effective strategies to improve the structural stability of cathodes and block the direct contact between electrodes and electrolytes. 29–35 So far, various surface coating strategies have been implemented to improve the structural stability of layered oxide cathodes. Liu et al 36 revealed that the Li 2 TiO 3 coating layer on the pristine particles of Li 1.08 Mn 0.54 Co 0.13 Ni 0.13 O 2 can inhibit transition metal dissolution and suppress oxygen loss.…”
Section: Introductionmentioning
confidence: 99%